The Influence Of Learning Based Multimedia Presentation And Learning Motivation On Receiving Information Ability - ST., M.Pd, Lukmanulhakim (Jurnal Visi Ilmu Pendidikan, 2015)
This study aims to investigate the influence of learning based multimedia presentation and learning motivation on receiving information  ability by third grade of elementary school in Pontianak. The research design use 2 x 2 factorial. The sampling technique which  population sampling is 60 students in 2 class. Liliefors test was used to test data normality. Barlett test of Chi Square statistic was used for testing data homogeneity. Analysis of variance (ANAVA) was used to analyze data followed by two line. The finding in this research are: (1) Receiving information ability on  learning with animation class have superior or higher than dari Receiving information ability on  learning with image class; (2) There are interaction on  learning based multimedia presentation with learning motivation on receiving information ability; (3) Student have great learning motivation and learning with animation have superior than great learning motivation and learning with image; (4) Student have low learning motivation used learning with image have superior than student have low motivation used leaning with animation. The result of this research are expected to have implications for learning in classrooms for teacher and student.